Penatalaksanaan Terapi Latihan Pada Kasus Post Open Reduction Internal Fixation Fraktur Cruris 1/3 Distal Dengan Pemasangan Plate And Screw Di Rso Prof. Dr. Soeharso Surakarta - Rizkya, Rinta; , Maskun Pudjianto, S.MPh, M.Kes (2015)
Background: A fracture is a break of continuity of bone fragments of bone tissue structure may be shifted or complete fracture. Cruris are two long bones tibia and fibula.Namely the location of the distal third of bone fracture in the bone below 1/3. While the left is the left or the left leg that suffered fraktur. So cruris fracture is a fracture that occurs in the tibia and fibula. In these conditions needed for internal mounting plate and screw fixation form. Interventions used by the author of exercise therapy, in the form of active exercise, passive exercise, static contraction, and practice using crutches road Methods: This paper uses the case study method to management therapy 3 times Results: After therapy 3 times the result to a decrease in the degree of pain, pain silent T1 T3 48 mm to 30 mm, tenderness T1 61 mm to 42 mm, 82 mm motion pain to 68 mm. There is an increasing range of motion active ROM T1 S 0 0-20 0-0 0 to T3 S 5 0-20 0-0 0, ROM passive S 5 0-20 0-5 0 to S 10 0-20 0-5 0 , Decrease edema T1 63 cm to 60 cm. an increase in the functional activity of the road, of which have not been able to walk until he could walk using crutches. Has not obtained an increase in muscle strength Conclusion: From the research that has been done, as evidenced by the use of exercise therapy for 3 days modalities US and exercise therapy for 6 times obtained an increase in impairment therapy, functional limitation.